Redescription of Agrilus zanthoxylumi Hou & Feng, 1989 (Coleoptera: Buprestidae) based on newly designated neotype - Wang, Xiao-Yi; Cao, Liang-Ming; Yang, Zhong-Qi; Li, Meng-Lou (Zootaxa, 2026)
Prickly ash borer (PAB) Agrilus zanthoxylumi was first identified but undescribed by Mr. Tao-qian Hou, Zoological Institute, Chinese Academy of Sciences, in the 1980s. This specific name first appeared in the book Cultivation and pest control of Sichuan pepper by Li et al. (1989a) as A. zanthoxylumi Hou & Feng. We have made various efforts to find the original named specimens, but both Hou’s and Li’s specimens of this species were lost. This insect causes significant damage in prickly ash orchards across northwestern and southwestern China, becoming one of the important economic pests in the production of prickly ash pepper in China. Confusion and inconsistencies have persisted in the citation of the author(s) of the Latin name in various papers, although there are many reports on its biology, occurrence habits, and control techniques. In present article, the name of this Agrilus species is verified and determined as A. zanthoxylumi Hou & Feng, 1989, which was first cited in Li et al. (1989a). A neotype for this taxon is also designated. To help accurate identification of this species, the morphological characteristics of all life stages (adult, egg, larva, and pupa) of A. zanthoxylumi are redescribed based on the neotype and other specimens, and color photos are also provided.